2009
DOI: 10.1093/scan/nsn049
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic enhancement of amygdala responses to fear

Abstract: Multiple lines of evidence implicate the basolateral amygdala (BLA) and the noradrenergic (norepinephrine, NE) system in responding to stressful stimuli such as fear signals, suggesting hyperfunction of both in the development of stress-related pathologies including anxiety disorders. However, no causative link between elevated NE neurotransmission and BLA hyperresponsiveness to fear signals has been established to date in humans. To determine whether or not increased noradrenergic tone enhances BLA responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 57 publications
6
66
1
1
Order By: Relevance
“…During a categorization task with self-referential emotional words during fMRI, reboxetine induced changes in a frontoparietal cortical network (Miskowiak et al, 2007). The other studies focused on the amygdala during the perception of emotional facial movies (Onur et al, 2009, Kukolja et al, 2008, the former reporting additionally increased activations in frontal, cingular, and occipital brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…During a categorization task with self-referential emotional words during fMRI, reboxetine induced changes in a frontoparietal cortical network (Miskowiak et al, 2007). The other studies focused on the amygdala during the perception of emotional facial movies (Onur et al, 2009, Kukolja et al, 2008, the former reporting additionally increased activations in frontal, cingular, and occipital brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have already reported that MDMA (10 mg/kg) increased hypothalamic noradrenergic activity (3). Limbic brain areas, such as hypothalamus, amygdala and hippocampus, exhibit rapid and large increases in noradrenaline turnover in anxiogenic situations (32,34). The mesolimbic dopaminergic system has already been related to anxiety-like responses (35).…”
Section: Mdma Increases Serum Corticosterone Levelsmentioning
confidence: 99%
“…This effect appears to be independent of the clinical (therapeutic) action, because it also occurs in healthy individuals. [8][9][10]12,48,49 The absence of differences in demographic variables and clomipramine doses between the two groups, whose components were free for personal or family history of psychiatric disorders, indicate that the distinct mood-related and brain activity changes detected in the responder subjects were not due to pharmacokinetic or subclinical factors. Rather, they may conceivably be related to genetic variations in patterns of drug response or 5-HT turnover.…”
Section: Discussionmentioning
confidence: 99%